Very high cycle fatigue of high carbon chromium bearing steel at high compressive mean stresses. (April 2023) - Fitzka, Michael; Moalla, Mourad; Mayer, Herwig
Highlights: Ultrasonic fatigue tests with σ min at the compressive yield stress are realized. High carbon chromium steel is tested at high compressive mean stresses and R  = −1. Fatigue limits are found for high compressive mean stresses but not for R  = −1. Damaging effect of inclusions can be quantified considering them as initial cracks. Kmax below effective threshold stress intensity means loading below the fatigue limit. Abstract: Very high cycle fatigue (VHCF) of high carbon chromium bearing steel 100Cr6 (SAE 52100; JIS SUJ2) is investigated with ultrasonic fatigue testing for compressive mean stresses with minimum stresses σ min at compressive yield stress σ CY, for σ min  = 0.59 σ CY, and for load ratio R  = −1. Fatigue limits are found for σ min  =  σ CY and for σ min  = 0.59 σ CY, whereas no fatigue limit below 10 9 cycles exists at R  = −1. Cracks leading to VHCF failures exclusively start at interior inclusions. Considering inclusions as cracks, the maximum stress intensity factor of a load cycle being below the effective threshold stress intensity factor determines the fatigue limit.